2001
DOI: 10.3758/bf03194434
|View full text |Cite
|
Sign up to set email alerts
|

Distinctiveness and serial position effects in tonal sequences

Abstract: The proportion-of-the-total-duration rule (Kidd & Watson, 1992) states that the detectability of a change in a component of a tonal sequence can be predicted by the proportional duration of the changed component relative to the length of the sequence as a whole. A similar viewpoint relies on temporal distinctivenessto account for primacy, recency, and other serial position effects in memory (Murdock, 1960;Neath, 1993aNeath, , 1993b. Such distinctiveness models predict that an item will be remembered if it is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 51 publications
(90 reference statements)
1
12
0
Order By: Relevance
“…If the subjects were visually, as well as auditorily, coding these items, then it would be no surprise to find SPFs that resembled visual SPFs. Another auditory experiment used lists of five different tones (Surprenant, 2001). Tone lists were presented in pairs, and the two lists were identical on half the trials.…”
Section: Discussionmentioning
confidence: 99%
“…If the subjects were visually, as well as auditorily, coding these items, then it would be no surprise to find SPFs that resembled visual SPFs. Another auditory experiment used lists of five different tones (Surprenant, 2001). Tone lists were presented in pairs, and the two lists were identical on half the trials.…”
Section: Discussionmentioning
confidence: 99%
“…As Dittrich and Oberfeld (2009) suggested, the primacy effect observed for the flat level profile could be explained by assuming that the segment levels are processed as serially sorted information, analogous to item lists in working memory (e.g., Postman & Phillips, 1965), where the characteristic serial position curve is observed. It has been suggested that the primacy and the recency effects observed in such experiments can be explained by temporal distinctiveness (e.g., Mondor & Morin, 2004;Murdock, 1960;Neath, 1993;Surprenant, 2001). According to this concept, beginning and end items of the stimuli have only one neighboring item and, therefore, are more distinct, resulting in better discriminability.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, since those authors motivated by theories of memory have speculated on the "distinctiveness" of certain events in the temporal sequence, such as the beginning and end of a sound ͑Neath et al., 2006;Surprenant, 2001͒, in Experiment 2 additional distinct events shall be experimentally induced by abruptly changing the spectral content of the sound to be judged. In particular, noise sequences will be designed that instantaneously shift from a low-pass to a highpass characteristic ͑and vice versa͒ in the middle of the temporal sequence.…”
Section: Rationalementioning
confidence: 99%